An Investigation of The Dominant Themes In Online Political Leadership Campaigns: A Case Study Of The OBIdient Campaign Discourse on X - Lily Chimuanya; Chika Tagbo; Samuel Owoeye (Ianna Journal of Interdisciplinary Studies)
Background: The persuasive function of language is perhaps most evident in political campaigns. The Nigerian political context is expected to reflect a robust adaptation of persuasion. Therefore, the OBIdient movement, a new phenomenon in the Nigerian political space, would offer an engaging framework for evaluating the persuasive dynamics of political communication in Nigeria.